5+3x+(-3)=x-(-4)

Simple and best practice solution for 5+3x+(-3)=x-(-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+3x+(-3)=x-(-4) equation:


Simplifying
5 + 3x + (-3) = x + -1(-4)
5 + 3x + -3 = x + -1(-4)

Reorder the terms:
5 + -3 + 3x = x + -1(-4)

Combine like terms: 5 + -3 = 2
2 + 3x = x + -1(-4)

Multiply -1 * -4
2 + 3x = x + 4

Reorder the terms:
2 + 3x = 4 + x

Solving
2 + 3x = 4 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
2 + 3x + -1x = 4 + x + -1x

Combine like terms: 3x + -1x = 2x
2 + 2x = 4 + x + -1x

Combine like terms: x + -1x = 0
2 + 2x = 4 + 0
2 + 2x = 4

Add '-2' to each side of the equation.
2 + -2 + 2x = 4 + -2

Combine like terms: 2 + -2 = 0
0 + 2x = 4 + -2
2x = 4 + -2

Combine like terms: 4 + -2 = 2
2x = 2

Divide each side by '2'.
x = 1

Simplifying
x = 1

See similar equations:

| 9x-8=6x+37 | | 5x-(-21)=x-(-19) | | -58=y/4 | | ((6-14)+4)*4= | | -58=-6y | | 5x-(21)=x-(-19) | | 14e^2+4x=112 | | x-(-5)=6x+10 | | 42/-6 | | a+b-a+2b= | | 1/5x+3=14 | | 4x^2-8x-77=0 | | 3x-(-1)=-16 | | 5+2y=6 | | 4x+6=24-2 | | 256*12x= | | 256*20= | | 5w-7w=4 | | 4z=1.8+3.8 | | 10/7*4 | | X-5x+3x-9x= | | 1.4(5x-.1)= | | 5/6k=7 | | -12-16*4= | | 4(z+6)-26= | | 4x/7x+28 | | 1-6x=19+3x | | 4x/27+8x | | 2(5z-1)-2(6-2z)=4 | | 3(2z-2)-3(5-3z)=3 | | 3y/4=0.6 | | 60-3(E-5)= |

Equations solver categories